An ingenious investigation on the adsorptive and antibacterial properties of a novel silver‑doped hydrochar - Suhas, Suhas (2024)
A novel silver-doped hydrochar (Ag-HC-230) was synthesized at 230 °C via hydrothermal carbonization of Tectona grandis seeds (TGs). The characteristic properties of the Ag-HC-230 were investigated using FTIR, XRD, TGA, SEM and surface area measurements. These results were further utilized for exploring the removal efficiency of the prepared material for chemical and biological contaminants. The surface area and pore volume of Ag-HC-230 were observed to be 24.9 m2g− 1 and 0.073 cm3g− 1, respectively. The ultimate analysis demonstrated that the prepared adsorbent was rich in C content (67.77%) as compared to N, H and S content. An ingenious investigation on the antibacterial and adsorptive performance of Ag-HC- 230 was evaluated too. The antibacterial performance of Ag-HC-230 was analysed by the agar well diffusion method against the cultured suspensions of S. aureus and E. coli. To provide a better insight of Ag-HC-230, the removal of acridine yellow G (AYG) was also studied and the experimental removal capacity was found to be 0.073 mmolg− 1 which was higher than undoped hydrochar HC-230-4 (0.058 mmolg− 1). The kinetic experimental data were tested by fitting with different kinetics models, and the PSO model was found to be effectively applicable. The adsorption data of AYG on Ag-HC-230 were evaluated using Temkin, Freundlich, Langmuir and D-R among which the data well fitted with the Langmuir model.